Ampicillin-Gentamycin Were Equivalent to Cefotaxime-Gentamycin Therapy Outcome on Neonatal Sepsis in Rural Area of West Borneo - Amelia Handoko; Jeremy Tentra Elnusa; Ferryna Novianita (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
The limited facilities in rural areas, such as Ketapang, make it hard for clinicians in charge to provide the most effective treatment while also considering preventing irrational antibiotic usage at once for neonatal sepsis. This study aimed to compare the length of stay of neonatal sepsis patients given Ampicillin-Gentamycin and Cefotaxime-Gentamycin as empiric antibiotic therapy. This was a retrospective observational study of patients admitted to Fatima Hospital, Ketapang, West Borneo, from June 2020-June, to 2021, with neonatal sepsis diagnosis based on the clinical presentation and routine blood lab. Slovin formula was used to determine the minimum sample size. Data were analyzed using Mann-Whitney Test. From 105 samples collected, the most common symptoms of neonatal sepsis found were fever (32.4%), vomitus (29.5%), and breathing difficulty (26.7%). Routine blood lab mostly showed leukocytosis with a mean of 28.369, and the mean length of hospitalization in patients given the Ampicillin-Gentamycin combination was 6.35 days. In comparison, the Cefotaxime-Gentamycin combination was 4.68 days. There was an insignificant difference in hospitalization between the two groups (p=0.274). Therefore, administration of Ampicillin-Gentamycin as empiric therapy in neonatal sepsis showed a good outcome as with Cefotaxime-Gentamycin therapy.